Twin study of impulsive buying and its overlap with personality - Bratko, Denis (Array, 2013)
This study explores the origins of individual differences in impulsive buying from a behavioral genetics perspective. It also assesses whether phenotypic associations between personality and impulsive buying tendency can be attributed to overlapping genetic factors. Data were collected via mail for 339 twin pairs. Personality traits according to a five-factor model and impulsive buying were measured. The results indicate that additive genetic, shared environmental, and nonshared environmental influences may be important for individual differences in impulsive buying. Phenotypic correlations with Impulsivity (r = .32), Neuroticism (r = .23), and Extraversion (r = .20) are largely driven by the overlapping genetic influences. Together with age and sex personality traits explain 25% of individual differences in impulsive buying tendency. These results add to our understanding of individual differences in impulsive buying and the nature of its relationship with personality.